2002
DOI: 10.1086/502070
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Surgical-Site Infections and Patterns of Antimicrobial Use in a Large Tertiary-Care Hospital in Ho Chi Minh City, Vietnam

Abstract: Our data show that (1) SSIs are prevalent at Cho Ray Hospital; (2) antimicrobial use among surgical patients is widespread and inconsistent with published guidelines; and (3) pathogens often are resistant to commonly used antimicrobials. SSI prevention interventions, including appropriate use of antimicrobials, are needed in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 19 publications
4
20
0
Order By: Relevance
“…[8][9][10][11][12] Some other workers have found Pseudomonas aeruginosa as the principal offender of SSI. 15,16 In our study gram negative bacilli were more predominant in the classes of wounds other than clean wounds. NNIS system data had revealed that gram positive pathogens were most frequently associated with SSIs.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…[8][9][10][11][12] Some other workers have found Pseudomonas aeruginosa as the principal offender of SSI. 15,16 In our study gram negative bacilli were more predominant in the classes of wounds other than clean wounds. NNIS system data had revealed that gram positive pathogens were most frequently associated with SSIs.…”
Section: Discussionsupporting
confidence: 47%
“…8 Another study reported a still higher resistance (92%) to gentamicin in gramnegative isolates. 15 In our study the sensitivity pattern to other aminoglycosides was 42.3% sensitivity to amikacin and netilmicin, 53.8% to kanamicin and 57.7% to tobramycin.…”
Section: Antimicrobial Susceptibility Pattern Of Gram Negative Isolatessupporting
confidence: 45%
See 2 more Smart Citations
“…In our series, the SSI rate in the elective surgery group was found as 10.9% similar to other studies, while in the emergency surgery group, the SSI rate was 26.7%. It is stated in the literature that the SSI rate increases 1.69 times for malignant neoplasms and 1.9-2.65 times for emergency procedures (40). In addition, SSI rate has been shown to increase 1.1-fold with every three-day admission.…”
mentioning
confidence: 98%